2020
DOI: 10.1590/1516-4446-2018-0325
|View full text |Cite
|
Sign up to set email alerts
|

Body self-image disturbances in women with prolactinoma

Abstract: To evaluate body dissatisfaction and distorted body self-image in women with prolactinoma. Methods: Body dissatisfaction and distorted body self-image were evaluated in 80 women with prolactinoma. All patients were in menacme, 34% had normal body mass index (BMI), and 66% were overweight. Most patients (56.2%) had normal prolactin (PRL) levels and no hyperprolactinemia symptoms (52.5%). The Body Shape Questionnaire (BSQ) was used to assess the patients' dissatisfaction with and concern about their physical for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…About half of the women reported still having hyperprolactinemia related symptoms after treatment and those women reported higher incidence of body dissatisfaction than women without symptoms. They also found that distorted self-image was more common in the group of women without symptoms related to hyperprolactinemia 35 . In our study, all women were untreated, and we did not measure body dissatisfaction in the same way as Pereira et al did.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…About half of the women reported still having hyperprolactinemia related symptoms after treatment and those women reported higher incidence of body dissatisfaction than women without symptoms. They also found that distorted self-image was more common in the group of women without symptoms related to hyperprolactinemia 35 . In our study, all women were untreated, and we did not measure body dissatisfaction in the same way as Pereira et al did.…”
Section: Discussionmentioning
confidence: 95%
“…One important finding in our study was that physical symptoms related to bodily changes were reported by more than half of the women. In a study by Pereira et al [35] body dissatisfaction and a distorted body self-image were evaluated in 80 women with either surgery or medical treated prolactinoma. About half of the women reported still having hyperprolactinemia related symptoms after treatment and those women reported higher incidence of body dissatisfaction than women without symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationships between PRL and anxiety and depression in prolactinoma patients remain to be explored. It has been reported that prolactinoma patients may experience dissatisfaction with their body image due to weight gain, and symptomatic patients have a higher rate of body dissatisfaction than asymptomatic patients ( 4 ). Prolactinoma patients often exhibit symptoms of depression, hostility, irritability, and anxiety ( 5 , 6 ), and stress may trigger neuroendocrine changes involving dopamine or serotonin, thus affecting the release of PRL ( 7 ).…”
Section: Introductionmentioning
confidence: 99%